Science literacy skills through the experience of project activities with assisted local potential based learning materials - Diana Hernawati; Mohamad Amin; Mimien Henie Irawati Al Muhdhar; Sri Endah Indriwati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
Scientific skills literacy is one of the skills that students need to have to support the learning process. This study aims to explain the literacy skills of the students through project experience with the help of local potential-based teaching materials. This research is a quantitative study and it used quasi-experimental design, pre-and posttest design. ANCOVA analysis was used as the data analysis technique at a significant level of 5% (p < 0.5). Analysis prerequisite tests included the Kolmogorov-Smirnov test for normality test and homogeneity of variance with Levene's-Test. All data testing was done using the SPSS version 23.0 for Windows. The results of the study show that the experience of project activities has a significant effect on the scientific literacy skills in three competencies. These competencies are to explain scientific phenomena, evaluate and design scientific investigations and interpret scientific evidence and data. Competence in evaluating and designing scientific investigations has the greatest significance compared to the other two competencies.